Preparation of an Immobilized Lipase-Palladium Artificial Metalloenzyme as Catalyst in the Heck Reaction: Role of the Solid Phase - Filice, Marco; Romero, Óscar; Aires, Antonio; Guisán, José Manuel; Rumbero, Ángel; Palomo, José Miguel (Advanced Synthesis & Catalysis, 2015)
A p-nitrophenylphosphonate palladium pincer was synthesized and selectively inserted by irreversible attachment on the catalytic serine of different commercial lipases with good to excellent yields in most cases. Among all, lipase from Candida antarctica B (CAL-B) was the best modified enzyme. The artificial metalloenzyme CAL-B-palladium (Pd) catalyst was subsequently immobilized on different supports and by different orienting strategies. The catalytic properties of the immobilized hybrid catalysts were then evaluated in two sets of Heck cross-coupling reactions under different conditions. In the first reaction between iodobenzene and ethyl acrylate, the covalent immobilized CAL-B-Pd catalyst resulted to be the best one exhibiting quantitative production of the Heck product at 70°C in dimethylformamide (DMF) with 25% water and particularly in pure DMF, where the soluble Pd pincer was completely inactive. A post-immobilization engineering of catalyst surface by its hydrophobization enhanced the activity. The selectivity properties of the best hybrid catalyst were then assessed in the asymmetric Heck cross-coupling reaction between iodobenzene and 2,3-dihydrofuran retrieving excellent results in terms of stereo- and enantioselectivity. This work has been sponsored by CSIC. M.F. thanks CSIC for a JAE‐Doc contract (“Junta para la Ampliacion de estudios”) cofounded by ESF (European Social Fund). O. Romero is grateful to CONICYT and Programa Bicentenario Becas‐Chile for financial support The authors also thank Dr. Ramiro Martinez from Novozymes for the generous gift of lipases and Dr. Daminatti from Resindion for the gift of the Sepabeads resin. Peer Reviewed